Načrtovanje in izgradnja relacijske podatkovne baze za funkcionalna živila - Juvan, Simona (Acta agriculturae Slovenica, 2005)
We present design and construction of a relational database for functional foods which are defined as foods used in everyday diet, and having beneficial effects on health as well as reducing risks for diseases. Database was designed according to Fienkelstein. It contains entities, attributes, and primary keys. Main entities are represented by: biologically active compounds, classification, properties, foods, physiological effects, diseases, processes, legislation, bibliography, and functional classification. Database was normalised and was constructed with MS Access 2000. It is based on dictionary of entities, attributes, relations, and entity-relationship diagram. It contains data for 35 biologically active foods. Classification tree was set up on the basis of descriptors from FSTA thesaurus following a bibliometric analysis. The data were extracted from 140 documents (articles, books etc.). The database is represented with six inter-linked forms (sheets): Classification, Biologically active compounds, Foods, Diseases, Legislation, Bibliography and Retrieval (Search). It is possible to search according to the following queries: (1) what are functional foods, (2) which active compounds are contained in foods, (3) classification of compounds, (4) which are the risk-reducing compounds, (5) phzsico-chemical properties of compounds, and (6) legislation in the field of functional foods.
Keywords: podatkovne zbirke; bibliografske podatkovne zbirke; načrtovanje; zbiranje podatkov; obdelava podatkov; klasifikacija; znanstvena informatika; bibliometrija; funkcionalna živila; zdrava hrana